PENGARUH PEMBERIAN EKSTRAK DAUN BINAHONG (Anredera cordifolia (Ten.) Steenis) DALAM AIR MINUM TERHADAP BOBOT HIDUP, BOBOT KARKAS DAN GIBLET BROILER - Imam Wahyudi; Rr. Riyanti; Purnama Edy Santosa (JURNAL ILMIAH PETERNAKAN TERPADU, 2015)
Binahong is a medicinal plant that grows in the lower mainland and the plateau that has a lot of benefits in curing various diseases mild or severe. One of this plant’s partis very useful,especially the leaves, because they contain some active compounds that are beneficial to health such as flavonoids, alkaloids, triterpenoids and saponins. This study aims to: 1) determine the effect of binahong leaf extract in drinking water on live weight, carcass weight and giblet broiler; 2) determine the best binahong leaf extract in drinking water to live weight, carcass weight, giblet broiler. The research was conducted on 10th June to 8th July, 2014 at henhouse Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. The method of research used completely randomized design (CRD), consist of 5 treatments and 4 replications. Each replication consist of 5 chickens per plot. The treatments were: 1) R0: 0 mg / kg body weight; 2) R1: 100 mg / kg body weight; 3) R2: 150 mg / kg body weight; 4) R3: 200 mg / kg body weight; 5) R4: 250 mg / kg body weight. The data obtained were analyzed by using ANOVA at 5% level. If the analysis shows real results, then continued with Least Significant Beta Test (BNT) at 1% or 5%. The results showed that: (1) the effect of leaf extract binahong 100-250 mg / kg of body weight in drinking water were significantly different (P <0.05) on live weight, carcass weight, and giblet broiler (2) binahong leaf extract in drinking water at 100-250 mg / kg of body weight caused lower body weight, carcass and giblet broiler if compared with controls.